Fish Catches Characterization on a Fixed Lift Net with RGB-LED intensity based on Pulse Width Modulation in Banten Bay - Riska Fatmawati; Mochammad Riyanto; Ronny Irawan Wahju (Fakultas Perikanan dan Kelautan, Universitas Riau, 2023)
The application of a fixed lift net using a Light Emitting Diode (LED-RGB) based on the Pulse Width Modulation (PWM) is one of the optimal fishing methods. The impact of the application of LED-RGB affects the catches in Banten Bay. The study aimed to identify the catches on fixed lift nets by using LED-RGB based on the PWM system. An experiment was direct data collection in Banten Bay, then the catch composition was analyzed by paired sample t-test with α 95% interval. The results showed that the number of catches on LED-RGB was significantly different from the number of catches on 4U fluorescent, while the types of catches were almost the same. The composition of fish species caught by LED-RGB was about 24 species and 4U fluorescent (22 species). The average percentage of fish species composition in LED-RGB lights was higher at 16,09% in Selaroides leptolepis species at 95 PWM intensity, compared to 4U fluorescent, the highest was Moolgarda seheli (13,27%).